Fongs nous o poc citats de Catalunya i Andorra, II - Vila i Garcia, Jordi; Rocabruna i Llavanera, August; Llistosella i Vidal, Jaume; Tabarés Carriedo, Manuel; Llimona i Pagès, Xavier; Hoyo Navarro, Pilar (Revista Catalana de Micologia, 2007)
New or rarely recorded fungi from Catalonia and Andorra, II. Account of 8 species of Ascomycetes and 48 species of Basidiomycetes selected from our recent collections, mainly made in SW Catalonia and in the Pyrenean range. Of special taxonomic and chorologic interest are: Rutstroemia luteovirescens (Rob. ex Desm.) White, Urnula craterium (Schw.) Fr., Amanita brunneoconulus Bas et Groger, Boletus junquilleus (Quél.) Boud., Coprinus idae Uljé, Hohenbuehelia cf. angustata (Berk.) Sing., Melanoleuca nauseosa (Boekhout) Bon, Mycena maurella Robich, Oudemansiella caussei (Maire) Moser ex Clémençon, Rugosomyces fallax (Peck ex Sacc.) Bon, Russula poichilochroa Sarnari f. eliochroma Samari and R. Werneri Maire.